Evaluation of the Anti-Inflammatory Effect of Dipyridamole, ATP per se and in Combination with Methotrexate in Freund’s Adjuvant Induced Arthritis in Rats - Manoj G. Tyagi, L.N. Babu and (Recent Research in Science and Technology, 2010)
Rheumatoid arthritis (RA) is a chronic inflammatory disease which mainly affects synovial joints and leads to damage of articular cartilage and ankylosis of joints. The effect of various drug interventions like the methotrexate, dipyridamole and ATP alone and in combination on RA were studied. RA was introduced with the help of Freund Ã¢â‚¬â„¢s adjuvant (0.5ml/200gms wistar rat) inÃ‚Â 6Ã‚Â Separate Wistar rat groups. Freund Ã¢â‚¬â„¢s complete adjuvant (FCA) is the combination of mineral oil, an emulsifier mannide monooleate with 1mg/ml heat killed dry mycobacterium tuberculosis H37Ra. The mycobacterium stimulate the immune system and enhance the immune response. On 11th day after FCA the various animals groups were treated with drug interventions and after 10 days of treatment the paw edema of the respective rats were assessed by a mercury displacement plethysmograph (INCO Corp., India). During these studies the changes in paw edema by drug treatment of animals were analyzed. The results of this study are discussed in this article.